The special vigilance of the Diocesan Bishop on the Monasteries sui iuris - Roca, M.ª José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This study analyzes how it articulates the obligation of the diocesan bishop provided in c. 386§2 CIC with due respect for the autonomy of the monasteries sui iuris. The duties of the Bishop regarding the custody of the faith in his diocese, the custody of contemplative charisms and the special vigilance of the diocesan bishop (c. 615) to protect an autonomous monastery allow the adoption of prudent measures even of a punishment nature, in cases of statements contrary to the faith by a religious of a monastery sui iuris. The particular law of the monastery must be respected, if it contains any specific provisions regarding the common law of the CIC. He must also hear the person concerned and communicate his decision in writing, stating the reasons for it. In this way, the right to appeal to higher authorities is guaranteed.
Keywords: the special vigilance of the diocesan bishop; autonomous monastery; integrity and unity of the faith